Effective Factors on Occupational Burnout among the Operating Room Staff in Teaching Hospitals affiliated with Isfahan Medical University: A qualitative content analysis - Mahmood Keyvanara; Nasrin ShaarbafchiZadeh; Mohammad Alimoradnori (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Burnout has negative effects on the performance of employees, especially on the operating room personnel, who are in contact with acute patients. The aim of this study was investigating effective factors on occupational burnout among the operating room staff at the teaching hospitals affiliated with Medical University of Isfahan, Iran. Methods: This study was a qualitative content analysis. The study had 20 participants selected from hospital managers, clinical supervisors, operating room supervisors, and hospital matrons in teaching hospitals (al-Zahra, Khorshid, Amin, Kashani, Feyz) of Isfahan in 2016.Participants were selected using the purposeful sampling method until information saturation was reached. Data were collected using a deep semi-structured interview, after thatall interviews were recorded and then transcribed and reviewed. Later, the data were analyzed by MAXQDA/12. Results: In this study, three main themes were achieved internal factors of organization, external factors of organization, as well as individual and personal factors of organization. Totally, these main themes had 51 subthemes. In the process of analyzing the main themes, we found that internal factors of organization had 37 subthemes, external factors of organization had 11 subthemes, and individual and personal factors of organization had three subthemes. Conclusion: Various factors related to job burnout were mentioned by decision makers. It is possible to resolve these factors by proper decisions of managers and heads of hospitals. Managers of hospitals should advance service quality, reduce costs, and decrease losses of burnout due to internal factors of organization, external factors of organization, as well as individual and personal factors of organization.